Non-Formal Primary Education (NFPE) annual report 1993 - BRAC (© BRAC, 2016)
1. Introduction 2. The BRAC School 3. Programme management and supervision 4. The training component 5. The programme till 1992 6. The progress in 1993 7. Monitoring and evaluation 8. Programme experimentations 9. The scholarship programme 10. Urban schools.